Learning Perl - Schwartz, Randal L. ([Place of publication not identified] : O'Reilly, 2010)
"In this video, Perl expert and co-author of the bestselling Learning Perl, Randal Schwartz, presents a sophisticated introduction to the language. This tutorial is designed to meet the pace and scope sought by today's programmers. You'll encounter detailed descriptions, thorough examples, and eclectic wit. Perl is the language for people who want to get work done. And this video covers all the important aspects of the Perl language through version 5.10. It will turn you into a Perl programmer"--Resource description page (viewed Jan. 24, 2011).
Presenter, Randal Schwartz.
Keywords: Perl (Computer program language); Perl (Langage de programmation); Perl (Computer program language)